Resistance of B-Cell Lymphomas to CAR T-Cell Therapy Is Associated With Genomic Tumor Changes Which Can Result in Transdifferentiation. (18th June 2022) - Laurent, Camille; Syrykh, Charlotte; Hamon, Maxime; Adélaïde, José; Guille, Arnaud; Escudié, Frederic; Jalowicki, Gael; Fina, Frederic; Bardet, Alexandre; Mescam, Lenaïg; Molina, Thierry J.; Dartigues, Peggy; et al.
Abstract : Despite the impressive efficacy of chimeric antigen receptor (CAR) T-cell therapy (CART) in B-cell non-Hodgkin lymphomas, durable responses are uncommon. The histopathologic and molecular features associated with treatment failure are still largely unknown. Therefore, we have analyzed 19 sequential tumor samples from 9 patients, prior anti-CD19 CART (pre-CART) and at relapse (post-CART), using immunohistochemistry, fluorescence in situ hybridization, array comparative genomic hybridization, next-generation DNA and RNA sequencing, and genome-scale DNA methylation. The initial diagnosis was diffuse large B-cell lymphoma (n=6), double-hit high-grade B-cell lymphoma (n=1), and Burkitt lymphoma (n=2). Histopathologic features were mostly retained at relapse in 7/9 patients, except the frequent loss of 1 or several B-cell markers. The remaining 2 cases (1 diffuse large B-cell lymphoma and 1 Burkitt lymphoma) displayed a dramatic phenotypic shift in post-CART tumors, with the drastic downfall of B-cell markers and emergence of T-cell or histiocytic markers, despite the persistence of identical clonal immunoglobulin gene rearrangements. The post-CART tumor with aberrant T-cell phenotype showed reduced mRNA expression of most B-cell genes with increased methylation of their promoter. Fluorescence in situ hybridization and comparative genomic hybridization showed global stability of chromosomal alterations in all paired samples, including 17p/ TP53 deletions. New pathogenic variants acquired in post-CART samples included mutations triggering the PI3K pathway ( PIK3R1, PIK3R2, PIK3C2G ) or associated with tumor aggressiveness ( KRAS, INPP4B, SF3B1, SYNE1, TBL1XR1 ). These results indicate that CART-resistant B-cell non-Hodgkin lymphomas display genetic remodeling, which may result in profound dysregulation of B-cell differentiation. Acquired mutations in the PI3K and KRAS pathways suggest that some targeted therapies could be useful to overcome CART resistance.